The effect of surlactin produced by Lactobacillus acidophilus on eye infectious bacteria in rabbits (Baghdad Science Journal, 2013)
Twenty five vaginal swabs from outpatients' healthy women were collected from Kamal Al-Samarai Hospital, Baghdad, to isolate and identify of Lactobacillus acidophilus. Three isolates were diagnosed as L. acidophilus which represents 15% of the total number of lactic acid bacterial (LAB) isolates; other LAB types represent 65% (20 isolates).The ability of L. acidophilus to produce surlactin was detected after measuring its biological activity to inhibit the adhesion of biofilm formed by Pseudomonas aeruginosa to surfaces using test tube method. It was found that all isolates were able to produce surlactin but the activity of surlactin was varying in each isolate. Surlactin produced by isolates 1 and 13 was the most effective. Biological applications of surlactin were studied by inhibiting the adhesion of pathogenic P. aeruginosa producing biofilm on contact lenses. In this study the surlactin has the ability to inhibit the adhesion up to 60% and 55% for isolates 1 and 13 respectively and does not have an antibacterial activity.Surlactin showed an ability to treat the infection in rabbits' eyes with P. aeruginosa while it did not show this ability against Staphylococcus aureus. Additionally, it prevented the infection with P. aeruginosa when administrated to rabbits' eyes inoculated with these bacteria only, while it showed no effect against S. aureus.